Protection of Industrial Design Law in the Enhancement of Economic Development in Indonesia (Faculty of Law, Universitas Negeri Semarang, 2019)
Legal protection of Industrial Design in Indonesia through Law Number 31 of 2000, the government's determination to protect the right holders of Industrial Design from various forms of violations such as plagiarism, piracy or imitation. The more comprehensive safeguards are expected to be a driving factor to increase the creativity of designers. This research is legal research in a normative juridical study with the consideration that the starting point of the research analysis of legislation is the rules regarding intellectual property rights. Industrial Design Arrangements within the framework of the Law on Intellectual Property Rights are inseparable from Indonesia's participation in international agreements in the field of trade, by participating in the WTO agreement, Indonesia has ratified the WTO with Law Number 7 of 1994. Indonesia must impose TRIPs as provisions governing Rights Intellectual Property. The existence of industrial design laws provides protection to designers to prevent and resolve disputes in the field of Industrial Design to the right holders of Industrial Design to make designers to be more creative and productive in creating and producing. The legal arrangement of Industrial Design which is most important in filing rights is related to the element of novelty in the creation of works of Industrial Design. The Copyright Approach in Industrial Design is when an Industrial Design is registered, it will immediately get protection. Where the priority is the originality of a Design. The Patent approach used is in terms of new requirements and substantive examination.Â Keywords: Industrial Design, Legal Protection, IndonesiaÂ